Studies on phytosterol content of Parkia roxburgii G. Don - DJADJAT TISNADJAJA; SUCI LESTARI HIDAYAT; SUKMA SUMIRJA; PARTOMUAN SIMANJUNTAK (Biodiversitas Journal of Biological Diversity, 2006)
Kedawung (Parkia roxburgii G. Don.) is one of plants that originally could be found in almost all parts of Java Island. Due to lack of attention, at present situation this plant could be categorized as an endangered species. This plant species distributed widely in Africa. In several African countries, this plant has an important position either as food resource or alternative medicine. In Indonesia, traditionally kedawung tree often use as medicine, especially as part of â€œjamu gendongâ€ formulation. This work was focused on the study of phytosterol content and it distribution. The research result show that almost all parts of kedawung tree have a significant content of phytosterol, which is dominated by beta-sitosterol. The highest beta-sitosterol content was founded in the stem of leaf (35.24% (w/w) and pod (29.67% (w/w). Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: endangered plant species, phytosterol, beta-sitosterol, traditional medicine.